Entrepreneurs and ritual in China's economic culture. Issue 5 (October 2019) - Herrmann-Pillath, Carsten; Feng, Xingyuan; Guo, Man
Abstract: Culture, mainly defined as values and beliefs, has recently attracted much attention in economics. Cultural practices receive less attention, as emphasized in anthropology. We argue that the notion of 'ritual' can enrich economic research on culture as a specific form of socially standardized interactions that create shared contexts and emotions to build mutual trust and community. China is an important case in point, because ritual is a central concern in common interpretations of traditional Chinese culture. We look at practices of Chinese entrepreneurs that activate rituals in various settings. We conclude that these phenomena can be analytically condensed in the cultural complex of a 'ritual economy'.